Best Practices for Data Structure Management - Bulusu, Lakshman (Oracle Embedded Programming and Application Development, 2011)
Data representation: database versus programming language perspectivesBest practices for using heterogeneous data structures: arrays, array lists, lists, maps, enumerationsBest practices for using LINQ to objects (in Oracle11g)Best practices for using objects as data structuresBest practices for metaprogramming: use or eliminateData structure management plays a primary role in managing data from the time the data is captured until it is transformed into presentable information, and it becomes a key driving factor for the efficiency of the (enterprise) solution being architected. As part of data integration or otherwise, data structure contributes a lot to the way changes are made in the database via applications. The proper selection of data structures and their use for the synchronization of data management optimizes the efficiency of the application. The union of co-existent technologies and deployment platforms calls for a “solution for coexistence” (e.g., using SOA-based services) for data management, that in turn escalate to efficient data structure architecture.